How residential CHPs could be integrated in renewable energy communities’ incentive schemes - Sforzini Matteo (EDP Sciences, 2021)
The present work aims to investigate the integration into renewable energy communities (REC) schemes of micro and mini- Combined Heat and Power (CHP) plants. In detail, it has been evaluated the minimum self-consumption (SC) share needed to even out the revenues coming from the energy efficiency certificates (EECs). In order to establish a SC based tariff for CHP plants a correlation between SC share and the tariff value has been assessed for different commercial plants. A 70% of SC share has been set as a minimum target, which is related to incentive rates of 53 and 39.5 €/MWh, for mini and micro-CHPs, respectively. These values are about 65% lower than the current tariffs set by ARERA (Italian Regulatory Authority for Energy, Networks and Environment) to reward the renewable energy SC. A real building and two CHP plants have been considered as reference case studies. A dynamic simulation has been carried out in order to analyse the proposed incentive scheme in a real application. Starting from a 3-D BIM model, the energy flows have been calculated over one year period. Finally, it has been demonstrated how a SC based tariff can significantly reduce the share of injected electricity into the grid, also promoting the thermal carrier sharing. In so doing, the renewable energy sources intermittency can be easily mitigated and balanced, avoiding additional burdens on public expenditure.